Beyond emissions: A comprehensive analysis of carbon tax as a catalyst for environmental and economic transformation in Indonesia - Wijaya, Suparna; Syakirarizki, Fairuz Geulish; Adhimar, Salsabila Syahda; Titania, Maharani; Berlin, Rona Aliyyah (WIM Solusi Prima, 2025)
Climate change and environmental degradation caused by carbon emissions have emerged as significant global challenges, prompting the search for effective fiscal policies for mitigation without impeding economic growth. This research critically analyzes the effectiveness and implications of carbon tax policies in Indonesia in reducing emissions and promoting environmental sustainability. Through a comprehensive systematic literature review approach, this study analyzes empirical evidence from various jurisdictions and models its potential impact in the Indonesian context. The results indicate that carbon tax implementation in Indonesia could reduce emissions by 3.2%-8.6% by 2030 compared to business-as-usual scenarios, with the greatest effects in the energy sector and carbon-intensive industries. Key findings suggest that optimal carbon tax design requires progressive rate structures, equitable revenue distribution mechanisms, and integration with complementary policy instruments. This research also identifies specific challenges for carbon tax implementation in Indonesia, including carbon leakage risks, distributional impacts, and institutional capacity limitations. The study contributes to the literature by offering a comprehensive framework for carbon tax policy reform that maximizes emission reductions while minimizing regressive economic impacts and optimizing environmental and health co-benefits.